Clinical Adaptation of the "Tibiofibular Line" for Intraoperative Evaluation of Open Syndesmosis Reduction Accuracy: A Cadaveric Study. (November 2016) - Reb, Christopher W.; Hyer, Christopher F.; Collins, Christy L.; Fidler, Corey M.; Watson, B. Collier; Berlet, Gregory C.
Background: The "tibiofibular line" is a new axial computed tomography parameter for assessing syndesmosis reduction, which references the flat anterolateral surface of the fibula and anterolateral tibial tubercle. These same bony landmarks are easily visualized via a lateral approach to the fibula. This cadaveric study assessed the practical aspects of measuring the tibiofibular line intraoperatively. Methods: Three observers simulated the tibiofibular line using operative rulers in 3 measurement series utilizing 10 cadaveric specimens: intact syndesmosis, syndesmosis reduction, and fixation after application of lateral plate and screws to the fibula, and post syndesmosis reduction and fixation without plate and screws. Results: The majority (78%) of clinical tibiofibular line measurements were within the "normal" range (0-2 mm). However, there was a general trend toward malreduction (>2 mm) across measurement series. Intraobserver variability ranged from poor to excellent (intraclass correlation range, 0.12-0.85, Fleiss kappa range, 0.19-0.40) and interobserver reliability was only generally in the fair range (intraclass correlation range, 0.49-0.61; Fleiss kappa range, 0.19-0.40). Conclusion: Taken as a whole, these findings found that the technique was feasible but clearly indicated that further refinement of this protocol, including the use of computed tomography, would be needed to determine if better control of confounding variables would reveal better observer reliability. Clinical Relevance: The CT-based TFL technique for syndesmosis reduction assessment could not reliably be translated into an intraoperative open technique because of the confounding effects of subjectivity and operator error.